Advances in cell therapy for orthopedic diseases: bridging immune modulation and regeneration - Wang, Jing; Xu, Shenghao; Chen, Bo; Qin, Yanguo (Frontiers in Immunology, 2025)
Orthopedic diseases pose significant challenges to public health due to their high prevalence, debilitating effects, and limited treatment options. Additionally, orthopedic tumors, such as osteosarcoma, chondrosarcoma, and Ewing sarcoma, further complicate the treatment landscape. Current therapies, including pharmacological treatments and joint replacement, address symptoms but fail to promote true tissue regeneration. Cell-based therapies, which have shown successful clinical results in cancers and other diseases, have emerged as a promising solution to repair damaged tissues and restore function in orthopedic diseases and tumors. This review discusses the advances and potential application of cell therapy for orthopedic diseases, with a particular focus on osteoarthritis, bone fractures, cartilage degeneration, and the treatment of orthopedic tumors. We explore the potential of mesenchymal stromal cells (MSCs), chondrocyte transplantation, engineered immune cells and induced pluripotent stem cells to enhance tissue regeneration by modulating the immune response and addressing inflammation. Ultimately, the integration of cutting-edge cell therapy, immune modulation, and molecular targeting strategies could revolutionize the treatment of orthopedic diseases and tumors, providing hope for patients seeking long-term solutions to debilitating conditions.